Documentation of the Mongolian khöömii repertoire: The music archives of the Mongolian Radio (Mongolian Journal of Arts and Culture, 2025)
Mongolian khöömii is a unique intangible cultural heritage that has been transmitted and developed through oral tradition for centuries. This study aims to document, classify, and introduce the archival collection of khöömii recordings preserved in the Musical Archives of the Mongolian National Public Radio (MNB Radio) into scholarly discourse. During the research process, khöömii-related recordings were identified and analyzed from a collection of over 3,000 Mongolian folk songs, including both long-song (urtyn duu) and short-song (bogino duu) recordings preserved in the MNB Radio archives. These recordings were classified based on chronology, thematic content, artistic performance, and instrumental accompaniment. Additionally, khöömii-focused content within the radio’s music and arts programs was cataloged and documented, contributing to a deeper understanding of the systematic evolution of the khöömii repertoire and its transmission. This study provides a structured documentation of the khöömii repertoire within the MNB Radio archives, highlighting its cultural significance and making it accessible for further academic and artistic research. Moreover, it serves as a fundamental resource for comparative studies on traditional and contemporary innovations in khöömii performance and composition.Монгол хөөмийн урын сангийн баримтжуулалт: МҮОНР-ийн хөгжмийн архивХураангуй: Монгол хөөмий нь ардын язгуур урлагийн хосгүй өв бөгөөд өнөөг хүртэл аман уламжлалаар дамжин хөгжиж ирсэн онцлогтой. Энэхүү судалгааны зорилго нь Монголын Үндэсний Олон Нийтийн Радио (МҮОНР)-ийн хөгжмийн фонд дахь хөөмийн баримтжуулалтад ажиглалт судалгаа хийж, тэдгээрийг нэгтгэн мэдээлж, эрдэм шинжилгээний эргэлтэд оруулахад чиглэгдэнэ. Судалгааны явцад МҮОНР-ийн эргэлтийн сан хөмрөг дахь 3000 гаруй монгол ардын богино болон уртын дууны бичлэгийн сангаас хөөмийн холбогдолтой бичлэгүүдийг шүүж, он дараалал, агуулга, уран бүтээлчийн гүйцэтгэл, хөгжмийн зэмсгийн хамсраа зэрэг үзүүлэлтээр ангилан шинжилсэн. Түүнчлэн радиогийн хөгжим-уран сайхны нэвтрүүлгүүдээс хөөмийн тухай контентыг мөн шүүж мэдээлсэн. Энэ нь хөөмийн урын сангийн хөгжлийн зүй тогтлыг илүү нарийвчлан судлах, өвлүүлэн түгээхэд ач холбогдолтой юм. Энэхүү судалгаа нь МҮОНР-ийн архивд хадгалагдаж буй хөөмийн урын сангийн үнэ цэнийг тодорхойлж, системтэй баримтжуулах, шинжлэх ухаан, судалгааны эргэлтэд оруулахад чухал хувь нэмэр оруулах төдийгүй хөөмийн уран бүтээлийн уламжлалт болон орчин цагийн шинэчлэгдсэн хэлбэрүүдийн харьцуулалт судалгаа хийх суурь мэдээллийг бүрдүүлэхэд чиглэгдэж байна.Түлхүүр үгс: хөөмийн уламжлалт урын сан, радио архив, дижитал хадгалалт, угсаатны хөгжим судлал